PROFIL KADER PEMUDA MUHAMMADIYAH SEBAGAI INTELEKTUAL INFLUENCER - Nuri, R Nurhayati; Ismail, Ismail; Nur, Makmur Jaya; Kusnadi, Kusnadi; Muyassarah; Haerati, Afnan (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
h